What Makes Students Successful in Online Learning? A Correlational Study of Satisfaction, Self-Regulation, and Grit - Ardiansyah, Arief; Akbar, Mukhammad Naafiu; Budiya, Bahroin (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
As a result of the spread of Covid-19, online learning is fast expanding in popularity throughout the world. To ensure that the learning process is effective, teachers must be aware of the personal factors that are associated with academic achievement. According to some theories, qualities such as learning satisfaction, self-regulated learning, and grit are all significant predictor variables of academic achievement in online learning. Among other things, the goal of this research is to ascertain the correlation between these three factors and academic achievement, identify their combined influence, and determine the extent to which each factor contributes to academic achievement. This study employs a quantitative methodology, employing a non-experimental correlation design with 153 students. Data on learning satisfaction, self-regulated learning, and grit were collected via a questionnaire survey, whereas data on learning outcomes were gathered from the results of the final semester exam. The collected data were then processed using multiple regression analysis statistical techniques. The findings of this study indicate that only learning satisfaction is strongly correlated with learning outcomes, that the three predictor factors together have little effect on learning outcomes, and that only learning satisfaction variables contribute the most to learning outcomes. This research uses a convenience sampling technique because the constraints on the researchers’ available time and resources. Therefore, future research should use more survey participants in order to achieve more robust inferences.